2018
DOI: 10.1097/md.0000000000012730
|View full text |Cite
|
Sign up to set email alerts
|

Regaining body weight after weight reduction further increases pulse wave velocity in obese men with metabolic syndrome

Abstract: Subjects with metabolic syndrome (MetS) or obesity have worse arterial stiffness. However, there have been no studies addressing time-sequential changes in pulse wave velocity (PWV) after weight loss and then regaining weight in obese non-diabetic men with MetS.We prospectively enrolled 40 obese, non-diabetic men with MetS undergoing a 3-month weight reduction program. Another 26 lean and healthy men were recruited for comparisons. Oral glucose tolerance test and brachial ankle (ba) PWV were assessed in study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Interestingly, brachial–ankle PWV at the 60th month after weight regaining in obese patients with MS was even worse than the baseline values, was associated only with SBP or DBP increments, and when compared to healthy individuals proves to be beyond the aging process. In addition, brachial–ankle PWV values after weight regaining were independent of body weight, high-sensitivity C-reactive protein (hs-CRP), or insulin resistance changes [ 56 ]. However, it is still unknown what impacts a decrease in PWV value after weight reduction the most; whether it depends on changes in adipokines and inflammatory markers or is due to weight reduction per se [ 57 , 58 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…Interestingly, brachial–ankle PWV at the 60th month after weight regaining in obese patients with MS was even worse than the baseline values, was associated only with SBP or DBP increments, and when compared to healthy individuals proves to be beyond the aging process. In addition, brachial–ankle PWV values after weight regaining were independent of body weight, high-sensitivity C-reactive protein (hs-CRP), or insulin resistance changes [ 56 ]. However, it is still unknown what impacts a decrease in PWV value after weight reduction the most; whether it depends on changes in adipokines and inflammatory markers or is due to weight reduction per se [ 57 , 58 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…Studies have suggested that BM cycling may be more deleterious than simply maintaining BM and may increase the risk of T2DM and cardiovascular disease (CVD). For example, in non-diabetic patients with MetS including obesity, BM regain after 60 months increased pulse wave velocity (PWV), a measure of arterial stiffness [61]. Additionally, follow-up studies after 4 [62], 10 [63] and 16 years [64] showed that higher BM fluctuations increased HOMA-IR and mortality [64], with the added detriments of increased SBP, total cholesterol, and TG [63] or higher risk for T2DM [62].…”
Section: Bm Cycling and Intermittent Fasting In Clinical Studiesmentioning
confidence: 99%
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
“…The durations of follow-up ranged from 1 to 60 months (median, 12 months). A total of 21 studies were from Western Europe, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 11 from North America, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 9 from East Asia, 29 , 38 , 39 , 44 , 51 , 52 , 60 , 66 , 68 5 from South America, 28 , 69 , 78 , 79 , 83 5 from Western Asia, 28 , 69 , 78 , 79 , 83 and 3 each from Africa, 35 , 50 , 76 the Pacific, 26 , 42 , 75 and Eastern Europe. 45 , 74 , 80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation